2023
DOI: 10.1021/acssensors.3c00774
|View full text |Cite
|
Sign up to set email alerts
|

Target-Driven Z-Scheme Heterojunction Formation for ppb H2S Detection from Exhaled Breath at Room Temperature

Abstract: As a biomarker of periodontitis, sensitive and timely monitoring of hydrogen sulfide (H2S) in exhaled breath at room temperature (RT) is important for the early intervention of oral diseases. However, the required high operation temperature to achieve high sensitivity is still a technical challenge for directly monitoring exhaled breath. In this study, by integrating metal–organic frameworks (MOFs) into self-aligned TiO2 nanotube arrays (NTs), a chemiresistor gas sensor with outstanding sensitivity and selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…However, despite having achieved a strong and fast sensing response, the poor humidity resistance remains a major challenge for MOS-based gas sensors. 35 Compared to the response at 25% RH, the NH 3 response was found to significantly decrease with increasing humidity (Figure S8). As shown in Figure 3d, a response of only ∼20% was retained upon exposure to high humidity conditions (75% RH), which greatly limited the application of the present sensor.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, despite having achieved a strong and fast sensing response, the poor humidity resistance remains a major challenge for MOS-based gas sensors. 35 Compared to the response at 25% RH, the NH 3 response was found to significantly decrease with increasing humidity (Figure S8). As shown in Figure 3d, a response of only ∼20% was retained upon exposure to high humidity conditions (75% RH), which greatly limited the application of the present sensor.…”
Section: ■ Results and Discussionmentioning
confidence: 93%
“…This could be attributed to the defective CeO 2 nanowires and perpendicular TiO 2 nanotube arrays, enabling effective exchange and transport of electrons. However, despite having achieved a strong and fast sensing response, the poor humidity resistance remains a major challenge for MOS-based gas sensors . Compared to the response at 25% RH, the NH 3 response was found to significantly decrease with increasing humidity (Figure S8).…”
Section: Resultsmentioning
confidence: 99%
“…The concentration of the interfering gas that we detected was higher than that of human exhaled breath (approximately 15 ppb–1.75 ppm), which clearly demonstrates the selectivity of this CSPH ion channel sensor. 51–59 The high selectivity of the CSPH ion channel-based sensor is mainly attributed to the material having two CO 2 binding sites, including the hydroxide ion and the tertiary amines on RhB, which greatly increases the ability to interact with CO 2 . In order to explore the effect of humidity, the CSPH ion channel-based sensor was placed at a relative humidity of 5–70% (RH), and then the response of 1000 ppm CO 2 was measured.…”
Section: Resultsmentioning
confidence: 99%
“…Although conventional gas detection methods, such as gas chromatography–mass spectrometry, quantum cascade lasers, infrared laser spectroscopy, and fluorescence spectrometry, provide high accuracy, these instruments are bulky, lack portability, and are expensive. Chemiresistive gas sensors, which are the most ubiquitous type of gas sensors, have garnered increased interest due to their rapid response, good accuracy, cost effectiveness, easy fabrication processes, and flexible configuration capabilities . Metal oxide semiconductors (MOS) have been widely used as gas sensing materials in chemiresistive gas sensors due to excellent sensing performance such as high sensitivity and fast response and recovery time. Among the diverse range of metal oxides, WO 3 is one of the most attractive MOS sensing materials in which the robust empirical evidence demonstrates its impressive sensitivity toward NO 2 , NH 3 , and volatile organic compounds (VOCs). , Its band gap energy of around 2.4 to 2.8 eV, and abundant oxygen vacancies suggest a significant promise for its application in H 2 S detection. , Unfortunately, pristine WO 3 does not respond well to H 2 S. For example, Urasinska-Wojcik et al reported a WO 3 -based sensor only exhibited a response ( R air / R gas ) of 1.4 toward 100 ppb H 2 S . Herein, several strategies from morphology to composition modulation have been proposed to modulate the material properties, which could contribute to the enhancement of gas sensing performance. ,, 1-Dimensional (1-D) nanostructures are highly considered as the top choice for gas sensing material morphology due to their large surface area to volume ratio that enhances their reactive and interactive potential .…”
mentioning
confidence: 99%